Difference in outcome event coverage between insurance-based and hospital-based databases: a methodological study of diabetes drug use and cardiovascular events in Japan - Ando, Takashi; Hasegawa, Tomoaki; Ishiguro, Chieko; Komiyama, Jun; Kuno, Toshiki; Iwagami, Masao (Frontiers in Pharmacology, 2025)
IntroductionIn countries with unrestricted access to healthcare, such as Japan, patients may initiate a drug at a clinic or hospital and then may visit another hospital when outcome events occur. Theoretically, an insurance-based database can capture all outcomes, whereas a hospital-based database can only capture outcomes when patients visit that hospital. We examined the difference in outcome event coverage between insurance-based and hospital-based databases in Japan, and its impact on pharmacoepidemiology studies, using diabetes drug use and cardiovascular events as an example.MethodsUsing the JMDC payer database, we identified new users of sodium-glucose cotransporter-2 (SGLT2) inhibitors or dipeptidyl peptidase-4 (DPP-4) inhibitors as the first choice of treatment for type 2 diabetes. Composite outcome was defined as the first hospitalization with a diagnosis of heart failure, stroke, or myocardial infarction. Among patients who initiated drug use at hospitals, we estimated the proportion of events captured in the same hospital among all events recorded in the insurance data. Subsequently, considering a hypothetical hospital-based database study (in which outcome events could only be captured in the same hospital), we estimated an adjusted hazard ratio (aHR) for SGLT2 versus DPP-4 inhibitors.ResultsThere were 72,556 and 39,214 new users of DPP-4 and SGLT2 inhibitors, respectively, with no history of cardiovascular events, including 18,325 and 9,478 who initiated treatments at hospitals, respectively. Among the 18,325 patients who initiated DPP-4 inhibitors, 195 events occurred, of which 94 (48%) could be captured in the same hospital. Among the 9,478 patients who initiated SGLT-2 inhibitors, 89 events occurred, of which 40 (45%) could be captured in the same hospital. The aHR (95% confidence interval) was 0.74 (0.49–1.12) in the hypothetical hospital-based database study, whereas it was 0.88 (0.64–1.21) in the insurance-based analysis. A sensitivity analysis restricted to hospitals in the Japanese Diagnosis Procedure Combination (DPC) system showed that the percentage exceeded 50% for both the composite and individual disease events.DiscussionThis Japanese study revealed that nearly half (over half when restricted to DPC hospitals) of cardiovascular events were captured in the same hospital where the diabetes drug was initiated.